Ainda que seja loucura, há nela certo método: o inconsciente segundo Matte-Blanco - Racy, Renan (2024)
The unconscious is one of the cornerstones of psychoanalytic theory. Proposed by Freud, this concept was established by the realization that perceptual data do not constitute the entire reality of the individual; there is a psychic reality formed by the image of the objective world, which does not completely correspond to it. The unconscious asserts that what is knowable is merely a fragment of the subject, not its entirety. Among the authors who developed the concept of the unconscious, building on Freud's theory, is Matte-Blanco. Part of a line of psychoanalysts who postulated that the unconscious possesses its own logic, the author utilized Freudian theory to develop original assumptions. However, his theory did not receive attention in Latin America. This work aims to present and explore the main concepts of this author’ theory, bringing to light a vast and influential body of work that remains largely unknown. For this purpose, it is essential to understand the historical context and the state of psychoanalytic theory at the time this work was developed. In contemporary clinical practice, we encounter patients who challenge the classic setting and the more orthodox psychoanalytic approach, referred to as borderline cases. The main premise of this work is that Matte-Blanco's theory offers an understanding of the logic of the unconscious that provides an innovative view of contemporary clinical practice, precisely because it sees the unconscious not as a structure, state, or energy, but as a logic of functioning. If the unconscious were entirely apprehensible, it would be conscious. If the unconscious were entirely inapprehensible and chaotic, the work of analysis would be impossible. Therefore, the unconscious must be governed by its own logic